Surah al-Hujurat: a charter of ideal social life - Shahed, Abul Kalam Muhammad; Osmani, Noor Mohammad; Siddique, Muhammad Abu Bakr (Bangladesh Institute of Islamic Thought (BIIT), 2015)
The main purpose of the research is to study Surah al-Hujurat of the Qur’an, which includes some fundamental principles and important rules and regulations for laying the foundations of an ideal society, which if followed properly, the society could live in peaceful harmony and mutual respect and love towards each other. Sayyid Abul A`la Mawdudi (1903-1979) and Sayyid Qutb (1906-1966) wonderfully explained those social etiquettes, norms and principles through their commentaries of the Qur’an. Both Tafsirs merged at some crucial points, and also differed at others. Since they lived in the contemporary ages, their Tafsirs have high impacts on the society and people today. They continue to influence society to a larger extent. The paper presents an introduction to Sayyid Mawdudi and Sayyid Qutb, their Tafasir and Surah al-Hujurat, fundamental guidelines and principles for ideal social system based on their tafasir while drawing the similarities and differences between both the scholars. The paper concludes that the Surah al-Hujurat contains important principles of Islam for a noble societal living, which if followed, the society turns into an ideal community, where all people live in perfect harmony, peaceful living, mutual respect and love.